Optimization of Renewable Energy Hybrid Power Systems Under Different Penetration and Grid Tariffs - Ozturk, Zafer; Demirci, Alpaslan (GAZI UNIV, 2023)
The trend towards renewable energy sources (RES) is increasing daily due to energy demand, costs, and environmental concerns. This study investigates the technical, economic, and environmental impacts of changes in energy costs and incentives on hybrid power systems (HPS). Optimization results show optimal HPSs vary between 75-200% penetration (PR) depending on grid energy tariffs and energy sales constraints (GSC). In these scenarios, the renewable fraction (RF) increased to 80%, while the excess electricity (EE) increased to 10%. On the other hand, energy tariffs and grid constraints limit the PR increase in the optimal scenarios. This reduced the RF by up to 26%, limiting the use of clean energy. Due to load mismatch and grid constraints, there was a minimal increase in RF after 200% PR. In addition, removing incentives increased the cost of energy (COE) and total net present costs (NPC) by up to 96%. The results show that grid constraints and energy tariffs directly affect the economic and environmental performance of renewable energy investments and can slow down the pace of these investments. Moreover, it has become clear that controlled incentive packages must continue to achieve zero carbon targets.
Keywords: Energy economics; hybrid power system; optimization; renewable energy; three-time tariff; BARRIERS; ISLANDS; Engineering